Mean pressure gradient effects on the performance of ramjet cavity stabilized flames - Morales, Anthony J.; Smerina, David M.; Thornton, Mason.R.; Rising, Cal J.; Sosa, Jonathan; Johnson, Ryan F.; Kessler, David A.; Goodwin, Gabriel; Ahmed, Kareem A. (Aerospace science and technology, 2023)
Premixed cavity stabilized flames are experimentally investigated in a high-speed ramjet engine under the influence of varying mean pressure gradients. The ramjet cavity incorporates a backward facing step with an aft ramp for flame stabilization in high Reynolds number. The ramjet engine is subject to varying wall geometry to form converging, diverging, and nominal configurations in order to investigate the effects of mean pressure gradients on engine performance. High-speed particle image velocimetry (PIV) and chemiluminescence imaging diagnostics are simultaneously employed to capture the reacting flow fields and flame dynamics. Imposing a larger favorable pressure gradient is shown to shrink the recirculation zone and alter shear layer dynamics, which leads to increased drag on the cavity. Additionally, inducing a stronger favorable pressure gradient is shown to excite a shear layer instability mode, characterized by a Strouhal number of St=0.1. Proper orthogonal decomposition (POD) results reveal that the instability mode is comprised of large-scale oscillations that occupy the entire cavity flow region, indicating that the excited oscillations are the manifestation of a global vortex shedding instability that occurs under non-reacting conditions. The results demonstrate that the performance and stability of the ramjet cavity flame can be influenced by the mean pressure gradient, which is vital for the design of high-speed air-breathing propulsion systems such as dual-mode scramjets.